PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA DOSEN DI UNIVERSITAS BINA BANGSA FAKULTAS EKONOMI DAN BISNIS - Angrian Permana (Universitas Mercu Buana, 2019)
The purpose of this study was to know the effect of motivation on the job satisfaction of lecturers at Bina Bangsa University Faculty of Economics and Business, to know the effect of compensation on lecturer satisfaction at Bina Bangsa University Faculty of Economics and Business, and to know the effect of motivation and compensation together on lecturers satisfaction at Bina Bangsa University Faculty of Economics and Business. This research method used quantitative methods with multiple regression models. The populations of this study were 98 lecturers and the samples used in this study were all lecturers. The results showed that motivation had an effect on lecturers job satisfaction, compensation did not affect on lecturers job satisfaction, also motivation and compensation had an effect on the work satisfaction of lecturers together